Dinamika Dan Tantangan Pendidikan Agama Islam Di Era Society 5.0 - Dinana, Retno Aqimnad; Fahmi, Muhammad; Rohman, Fathur (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2024)
This research aims to identify the dynamics of Islamic religious education in the Society 5.0 era as well as the challenges faced by Islamic educational institutions regarding curriculum and educator competencies. The methods used include literature studies and qualitative analysis, examining various relevant sources regarding the implementation of technology in education. The research findings indicate that technology plays a crucial role in supporting character education needed in this era, with concrete examples such as the use of AI-based learning applications that can enhance student engagement. The conclusion emphasizes the importance of developing a curriculum that integrates technology with religious values so that Islamic Religious Education (PAI) can shape a younger generation with strong character and balanced morals. The implications of this research highlight the need for training for educators in integrating technology into learning, as well as the importance of monitoring technology use to maintain spiritual and moral values in education.